Methoxyflurane Instead of Morphine in Acute Coronary Syndrome Patients: Results of the Randomized Controlled METHANE-SIRIO 4 Study - Niezgoda, Piotr; Podhajski, Przemysław; Kasprzak, Michał; Barańska, Malwina; Rakotoarison, Oscar; Karolko, Bożena; Pietrzykowski, Łukasz; Michalski, Piotr; Kosobucka, Agata; Sikora, Adam; Chałupka, Joanna; Marszałł, Michał; Kuliczkowski, Wiktor; Kubica, Aldona; Kubica, Jacek (Thrombosis and Haemostasis, 2025)
Morphine is known to negatively influence the pharmacokinetics (PK) and the antiplatelet effect of oral P2Y12 receptor inhibitors administered due to an acute coronary syndrome. Worldwide studies of the potential approaches to overcome the undesired morphine effect have been only partially successful. The aim of the METHANE-SIRIO 4 study was to evaluate the PK and pharmacodynamics of ticagrelor and its active metabolite in unstable angina (UA) patients treated with morphine or methoxyflurane.Consecutive patients diagnosed with UA, randomized into the study arms, underwent the assessment of platelet reactivity using the Multiplate analyzer at nine predefined study time points. Serum concentrations of ticagrelor and its active metabolite, AR-C124910XX, were measured for each study participant. Median platelet reactivity was significantly lower in patients who received ticagrelor and methoxyflurane versus ticagrelor alone at 30 minutes postticagrelor loading dose. A trend toward lower reactivity was observed at 45 and 240 minutes. Significant differences in median serum concentrations of ticagrelor and its active metabolite were most pronounced between patients treated with ticagrelor and methoxyflurane versus ticagrelor and morphine.Co-administration of methoxyflurane in acute coronary syndrome patients allows for the avoidance of negative effects of morphine and has the additional effect of inhibiting platelet reactivity. Further randomized studies would be recommended to support these findings.
Keywords: acute coronary syndrome; unstable angina; methoxyflurane; morphine; platelet reactivity